Implementasi Teknologi GPS Tracking Smartphone Sebagai Aplikasi Monitoring Lokasi Anak - Ahyar Muawwal; Baizul Zaman (STMIK KHARISMA Makassar, 2017)
Parents have a very important responsibility in shaping the attitude and behavior of their children. parents can, shape their child's behavior by monitoring their daily activities, such as where he or she goes and what locations the child has visited. but sometimes from every parent can not control the child who went anywhere because of busy and sometimes the child who was asked could lie. To assist in supervising the child in his or her daily activities, especially the location of the site, it is necessary to have a location monitoring system or child position monitor based on the android smartphone that it uses with the utilization of Global Positioning System (GPS) technology as a tracking device. With this child's location monitoring system, it can assist parents in knowing the locations their children have visited and displayed in the form of Google Maps interface so as to assist parents' supervision of their children inrealtime.